Effect of high-protein and low-carbohydrate diet on lipid and intestinal short-chain fatty acid secretion in C57BL/6 mice - HE Yuxi, LIU Ruonan, GONG Kai, YIMANALI Hulalai, LI Li, MAIMAITI Maiira, ZHAO Xiaoguo (Xin yixue, 2025)
Objective To investigate and formulate the healthy high-protein and low-carbohydrate diet pattern suitable for the normal weight group. Methods Twenty-four SPF grade male C57BL/6 mice aged 6 to 8 weeks （weighing 15 to 20 g） were randomly divided into the control group （Ct group）， 5% high-protein low-carbohydrate diet group （5%LCD group）， and 30% high-protein low-carbohydrate diet group （30%LCD group）， with 8 mice in each group. The mice were fed with a basic diet， 5% LCD， and 30% LCD for 4 weeks， respectively. The food intake， water intake， and body weight were observed， and the blood lipid indexes and the content of cecal short-chain fatty acids were measured. Results Compared with the Ct group， food intake in the 5%LCD and 30%LCD groups was increased （both P < 0.01）. Compared with the Ct group， the serum total cholesterol （TC） and low-density lipoprotein cholesterol （LDL-C） contents in the 5%LCD group were increased （both P < 0.05）， and the serum LDL-C and high-density lipoprotein cholesterol （HDL-C） levels in the 30%LCD group were increased （both P < 0.05）. Compared with the Ct group， the secretions of propionic acid， isobutyric acid， and isovaleric acid in the cecal contents of mice in the 5%LCD and 30%LCD groups were decreased （all P < 0.05）. Conclusion Based on a comprehensive assessment of body weight， lipid metabolism， and short-chain fatty acid secretion， 30% LCD is more suitable as an effective dietary recommendation due to its higher HDL-C levels.